Health for all: Reimagining Inclusive Healthcare Marketing for Rural India - Jain, Roopam; Hazra, Ayan (Journal of Neonatal Surgery, 2025)
The large rural population of India still faces major inequalities in accessing high-quality healthcare because of infrastructure, socioeconomic, and geographic constraints. This study investigates how inclusive healthcare marketing can be a game-changing strategy to eliminate these disparities and guarantee "Health for All" in rural India. The study uses a multidisciplinary approach to analyse existing healthcare outreach models, pinpoint the shortcomings of traditional marketing strategies, and suggest an inclusive framework that is community-driven, culturally aware, and technologically flexible. Low health literacy, the digital divide, affordability, and mistrust of official healthcare institutions are some of the major issues addressed in this article, which draws upon case studies, government reports, and healthcare marketing trends. It highlights how crucial it is to employ localized communication tactics, collaborate with grassroots groups, and speak in vernacular languages in order to establish relevance and trust. The potential of digital tools to democratize healthcare information and services is examined, including telemedicine, social media platforms, and mobile health applications. The study also identifies promising approaches that have demonstrated potential in improving healthcare delivery in rural areas, such as Accredited Social Health Activists (ASHAs), mobile health vans, and public-private partnerships. To guarantee long-term engagement and behaviour change, the suggested inclusive marketing strategy incorporates behavioral insights, sympathetic storytelling, and community co-creation. In the end, the study promotes a change from transactional marketing to transformative healthcare engagement, putting rural communities at the forefront of the development and application of strategies. In rural India, this rethought strategy may promote health equity and bring the goal of universal health coverage to life